Identification Of Superior Hybrids Among The Crosses Between Various Rice Genotypes (Applied Biological Research, 2014)
Three cytoplasmic male sterile (CMS) lines of rice i.e. IR58025A,  IR68897A and Pusa 6A were crossed with seven pollen parents (Sarjoo 52, Jaya, Sasyashree, Swetha, HUR 5-2, PR-106 and BPT 5204) into line  x tester design. In addition to the yield traits, mean performance for  grain quality characters were recoded in parents and all the 21 hybrids.  Based on their yield performance and grain quality features, only two  hybrid combinations, IR68897A X Jaya and IR68897A X BPT 5204  were identified to be superior as compared to their parents and the check variety. Both these hybrids can be recommended for the  commercial cultivation.
Keywords: Grain quality; hybrid; rice; yield performance